Sociodemographic Factors on Financial Literacy of University Students in Pekanbaru, Indonesia - Mimelientesa Irman; Suwitho Suwitho; Fadrul Fadrul (Yayasan Riset dan Pengembangan Intelektual, 2020)
This study aimed to investigate the effect of socio-demographic factors, including gender, work experience, age, and GPA (Grade Point Average) on the students’ level of financial literacy within some universities in Pekanbaru. This study conducted in two state universities (Riau University and UIN Sultan Syarif Kasim) as well as in four private universities (Caltex Polytechnic University, Muhamadiyah University of Riau, Lancang Kuning University, and STIE Pelita Indonesia). The universities were the object of this study since they had collaborated with the Riau Representative Indonesia Stock Exchange in establishing a financial education in the purpose to develop students’ knowledge on investment products and personal financial management. The population in this research was 78.540 active students and based on Slovin formula this study used 348 students as sample. Sampling technique used was simple random sampling. In addition, this study applied descriptive analysis and Binary Logistic Regression test as the data analysis technique. As the results, this research indicated that two factors, i.e. work experience and GPA significantly affected the students’ level of financial literacy. In contrast, other factors, i.e. gender and age did not affect the level of financial literacy of university students in Pekanbaru City.